How Thor lost his thunder - Taggart, Declan, author.
1 online resource (xiii, 213 pages)
Keywords: "How Thor Lost his Thunder is the first major English-language study of early medieval evidence for the Old Norse god, Thor. This geographically and chronologically far-reaching study considers the earliest sources in which Thor appears, including in evidence from the Viking colonies of the British Isles and in Scandinavian folklore. Through tracing the changes and variety that has occurred in Old Norse mythology over time, this book provokes a questioning of the fundamental popular and scholarly beliefs about Thor for the first time since the Victorian era, including whether he really was a thunder god and whether worshippers truly believed they would encounter him in the afterlife. It is ideal for scholars and students of mythology, and the history and religion of medieval Scandinavia"--Provided by publisher.